2020
DOI: 10.1101/2020.07.03.163634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Ceratodon purpureus genome uncovers structurally complex, gene rich sex chromosomes

Abstract: AbstractSex chromosomes occur in diverse organisms, but their structural complexity has often prevented evolutionary analyses. Here we use two chromosome-scale reference genomes of the moss Ceratodon purpureus to trace the evolution of the sex chromosomes in bryophytes. Comparative analyses show the moss genome comprises seven remarkably stable ancestral chromosomal elements. An exception is the sex chromosomes, which share thousands of broadly-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 120 publications
(34 reference statements)
4
38
0
Order By: Relevance
“…Empirical data derived from Marchantia polymorpha (Bowman et al, 2017) and Ceratodon purpureus (Carey et al, 2020) agrees largely with the theories in suppressed recombination on both U and V chromosomes with concomitant repetitive element acquisition. The presence of homologs between the U and V, known as gametologs, also supports the prediction that in a haploid organism the essential genes on sex chromosomes are more likely to persist.…”
Section: The Central Role Of Sex Chromosomes In Bryophyte Evolutionsupporting
confidence: 73%
See 4 more Smart Citations
“…Empirical data derived from Marchantia polymorpha (Bowman et al, 2017) and Ceratodon purpureus (Carey et al, 2020) agrees largely with the theories in suppressed recombination on both U and V chromosomes with concomitant repetitive element acquisition. The presence of homologs between the U and V, known as gametologs, also supports the prediction that in a haploid organism the essential genes on sex chromosomes are more likely to persist.…”
Section: The Central Role Of Sex Chromosomes In Bryophyte Evolutionsupporting
confidence: 73%
“…Compared with M. polymorpha, the sex chromosomes of C. purpureus show structural variation between the U and V to a similar extent, and highly differentiated transposable elements accumulation, but with the non-recombining regions younger (McDaniel et al, 2013a;Carey et al, 2020). Carey et al (2020) demonstrated that the sex chromosomes of C. purpureus expanded via at least two distinct chromosomal fusions to form neo-sex chromosomes and most of the numerous sex-linked genes to the non-recombining U and V are of recent recruitment. The authors suggest that the evolution of sexual dimorphism in bryophytes is largely driven by sexual antagonistic selection through sex chromosome rearrangement, including gene translocations and also sex chromosome translocations in some species (Carey et al, 2020).…”
Section: The Central Role Of Sex Chromosomes In Bryophyte Evolutionmentioning
confidence: 97%
See 3 more Smart Citations